Biomechanical analysis of the tuck jump assessment - Nascimento, N.; Sideris, V.; Read, P. J. (The Journal of Strength and Conditioning Research, 2022)
The tuck jump assessment (TJA) examines plyometric technique flaws associated with the increased risk of anterior cruciate ligament injury. Biomechanical data to investigate the mechanics used during the TJA are limited and assessing each jump individually across the entire test period is time inefficient. This study examined performance characteristics and movement mechanics in 16 professional soccer players during a standardized TJA protocol (10 jumps) to determine if sensitive periods exist within the test period (first 5 vs. last 5). Jump height, average power (PW) reactive strength index (RSI), frontal plane projection angle (FPPA), knee angular velocity (AV), and peak knee flexion angle (PKA) were analyzed using an optoelectrical and inertial measurement unit device. Jump height and PW increased in the past 5 jumps displaying a medium effect size (d = > 0.5). A trend was observed of increased AV, FPPA, and PKA during the past 5 jumps; however, no meaningful differences were observed between respective jump phases, and effect sizes were small (d = 0.2). This study indicates that performance metrics increase during the past 5 jumps of a standardized TJA 10-jump protocol; thus, analyzing the entire test period may not be required, providing a time-efficient approach. Caution should be applied if using this protocol as an injury risk screening tool or to identify fatigue related alterations in male professional soccer players as no obvious movement abnormalities were apparent and minimal differences were present between jump phases in a range of kinematic variables across the recorded test duration.